The emotional intelligence in talented students in Jordan - Al-Riggad, Hana Khalid (Arab Journal for Sciences and Research Publishing, 2016)
The current study aimed to identify the levels of emotional intelligence among talented students in Jordan, and the sample of the study consisted of (100) students from the tenth grade. The study tool consisted of a measure of emotional intelligence, which was developed by the researcher, and the sincerity and consistency of the study tool were verified. After conducting statistical analyses, the study found a high level of emotional intelligence among talented students, and the results showed no statistically significant differences depending on the educational level of the father in all fields except the field of pressure management and in favor of the university level of fathers, the study also found no differences in the areas of emotional intelligence depending on the level of income, and the study proposed a set of recommendations, including: strengthening the application of mechanisms of emotional intelligence within classrooms.
Keywords: emotional intelligence; students; gifted